The willingness to pay for conservation fee of urban green space: a case study of Kota Damansara Forest Reserve, Malaysia - Ab Razak, Nurshazwani; Mohammad Afandi, Syamsul Herman; W Mohamad, Wan Norhidayah (Human Resource Management Academic Research Society, 2023)
In recent years, Malaysia's total forest area has decreased due to rapid urban growth. Urban green spaces (UGS) act as forested land in a township. We assess the importance of UGS by estimating the visitors' willingness to pay (WTP) for a hypothetical conservation fee for Kota Damansara Forest Reserve (KDFR) in Kuala Lumpur, Malaysia. This study applied the Contingent Valuation Method (CVM), where the Double-bounded dichotomous choice (DBDC) format was adopted. Primary data were obtained from 400 recreationists within KDFR. Trained enumerators conducted interview sessions at main trailheads and recreational spots in KDFR. SPSS Statistical Software version 22 was employed for descriptive analysis of the respondents' socioeconomic characteristics. STATA 14 was used for multiple regression analysis and to estimate the willingness to pay. The findings show that recreationists in KDFR are willing to pay a conservation fee of RM 5.22 per person/visit. By multiplying the WTP with the population, the conservation value for 2020 is estimated at RM 243,907.80. The results of this study would specifically assist other government authorities in administering their land use when it involves recreational and conservation consumption in urban areas through financial information.